A Comparative Evaluation of The Practice of Self Medication In A Town of Western Maharashtra - Maria, C.; A. Pratinidhi, Dr. Shilpa (Journal of Medical Biomedical and Applied Sciences, 2018)
Background: Medical professionals are nowadays facing an increased trend of their patients finding a cure to their illnesses by themselves. This has been on the rise since past few years with the advancements in technology and information available to all about everything. Self-medication, if practiced in an uncontrolled pace can cause serious ill-effects as well as fatalities in the population.Objectives: To study the prevalence of the practice of self-medication in the rural and urban population of a small town in western Maharashtra and assess its features, frequency, etc. and also to correlate it with the patientâs education, occupation, opinion and reasons.Study Design: A total of 100 participants with 50 eachin the two groups - urban and rural population, were selected on a random basis from amongst the OPD visitors of Dr. Bhausaheb Sardesai Talegaon Rural Hospital, Talegaon Dabhade, Taluka Maval, pune. Study questionnaire was distributed to them and collected back with their responses. Responses were recorded and analysed to obtain the results.Setting: Out-Patient Department (OPD) of Dr. Bhausaheb Sardesai Talegaon Rural Hospital attached to MIMER Medical College, Talegaon Dabhade, Pune.Data Sources and Analysis: Data was obtained from the questionnaire responses and tabulated in Excel 2010. Further, analysis was done to estimate the prevalence and other features of self-medication.Results: 72.34 % of the urban participants and 70.73 % had the practice of self-medication. The various reasons for it include high fees charged in medical facilities, time-consuming visits, recurring minor illnesses and a lot more. Many considered this practice as a cheap, efficient and time-saving mode of treatment.Conclusion: There is an increasing trend of self-medication. If not controlled adequately, this can lead to a further rise in adverse drug reactions and drug resistance among the growing population which poses a serious threat to the medical professionals as well as the human inhabitants all over the world.